Loneliness and Facebook use: the role of social comparison and rumination. Issue 1 (January 2021) - Dibb, B.; Foster, M.
Abstract: There is conflicting evidence as to whether Facebook, one of the most popular social networking sites, either promotes social connectedness or contributes to the rising prevalence of loneliness. This study aimed to understand the association between Facebook use and loneliness. Two hundred and fourteen active Facebook users ( M age = 35.65; 80.8% female) completed a cross-sectional questionnaire measuring the nature of their Facebook use, how frequently they ruminate, the tendency to compare themselves to their Facebook friends, and upward and downward social comparison. The results showed that rumination and upward social comparison on Facebook were significantly associated with loneliness. The type of activity users engaged in when using Facebook was not significant. The study therefore demonstrates that Facebook users who ruminate and compare themselves to their perceived superiors on Facebook are more likely to experience loneliness. Suggested solutions include raising awareness and using algorithms on Facebook to deliver targeted interventions. Abstract : Loneliness, Social comparison; Rumination; Social media use, Facebook.